Masked Morphological Priming in German-Speaking Adults and Children: Evidence from Response Time Distributions - Hasenäcker, Jana; Beyersmann, Elisabeth; Schroeder, Sascha (Frontiers in Psychology, 2016)
In this study, we looked at masked morphological priming effects in German children and adults beyond mean response times by taking into account response time distributions. We conducted an experiment comparing suffixed word primes (kleidchen-KLEID), suffixed nonword primes (kleidtum-KLEID), nonsuffixed nonword primes (kleidekt-KLEID) and unrelated controls (träumerei-KLEID). The pattern of priming in adults showed facilitation from suffixed words, suffixed nonwords and nonsuffixed nonwords relative to unrelated controls, and from both suffixed conditions relative to nonsuffixed nonwords, thus providing evidence for morpho-orthographic and embedded stem priming. Children also showed facilitation from real suffixed words, suffixed nonwords and nonsuffixed nonwords compared to unrelated words, but no difference between the suffixed and nonsuffixed conditions, thus suggesting that German elementary school children do not make use of morpho-orthographic segmentation. Interestingly, for all priming effects, a shift of the response time distribution was observed. Consequences for theories of morphological processing are discussed.